THE INFLUENCE OF BRAND IDENTIFICATION AND BRAND SATISFACTION OF SMARTPHONE PRODUCTS ON BRAND EVANGELISM - Mamesah, Stefanus; Tumbuan, Willem J. F. A.; Tielung, Maria V.J. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Smartphones have become an inseparable object from the public, especially for students. However, the preferences of each student are different, and after using the product or the smartphone they choose, they will judge how well the smartphone is by comparing their expectations with the performance of the smartphone they are using. Campus life is a life of socializing between one student and another. With such a situation, there are not a few occasions where students exchange opinions and thoughts about things that are liked by one student to another, especially in this case, the matter of smartphones. This research aims to analyze the determinants that affect the Brand Evangelism within the students of FEB Unsrat, in this case are brand identification and brand satisfaction. This study uses quantitative methods with questionnaires used to collect data, this research uses Multiple Linear Regression as the tool of analysis. The sample of this research are 100 active students of FEB Unsrat. The findings revealed that both brand identification and brand satisfaction have positive relationship and significant influence toward brand evangelism. From the results, it is recommended to smartphone companies need to focus on how the company can make bonds with their consumer. Also, the marketeers of each companies need to listen to consumer on how they feel about the brand itself, so that the consumer will be satisfied with the products. Keywords: brand identification, brand satisfaction, brand evangelism